Molecular insights into the phylogenetic placement of the poorly known genus Niceforonia Goin & Cochran, 1963 (Anura: Brachycephaloidea) - Acosta-Galvis, Andrés R.; Streicher, Jeffrey W.; Manuelli, Luigi; Cuddy, Travis; de Sá, Rafael O. (Zootaxa, 2018)
Among New World direct-developing frogs belonging to the clade Brachycephaloidea (= Terraranae), there are several genera with uncertain phylogenetic placements. One notable example is the genus Niceforonia Goin & Cochran 1963, which includes three species that are endemic to Colombia. Three specimens of the species Niceforonia nana were collected and for the first time the genus is included in a molecular phylogenetic analysis of mitochondrial (mtDNA; 12S and 16S) and nuclear (nucDNA; TYR and RAG1) markers. Molecular phylogenetic inference based on concatenated and separate mtDNA and nucDNA analyses recovered Niceforonia nana nested within Hypodactylus Hedges et al. 2008, rendering the latter genus paraphyletic. Consequently, herein we place the genus Hypodactylus in the synonymy of Niceforonia to resolve the paraphyly and place Niceforonia in the subfamily Hypodactylinae. Based on our revised concept of the genus Niceforonia we conducted preliminary morphological comparisons using specimens and literature descriptions. Finally, Nicefornia nana is quite divergent from other species of Niceforonia (uncorrected genetic distances of ca. 10% 16S and 7% TYR) suggesting that further taxonomic revision may be warranted.